Kitâbü’l-fasl fi’l-milel ve’l-ehvâ’ ve’n-nihal - 880-01 İbn Hazm, 994-1064. ([Bağdat])
5 cilt 2 ciltte (1. c. 224, 4 sayfa, 2. c. 193 sayfa, 1, 2 sayfa ; 3. c. 264, 2 sayfa, 4. c. 227, 1 sayfa , 5. c. 144 sayfa)